PEMETAAN WILAYAH DAN KARAKTERISTIK KAJIAN FILSAFAT ISLAM MODERN (SUNNI DAN SYIAH) - Tanca, Syamsul; Harun, Hamzah; Latif, Muhaemin (Aqidah-ta: Jurnal Ilmu Aqidah, 2023)
This study aims to find out the history of the birth of Sunni and Shia and how the area and characteristics of the region and the study of Islamic philosophy according to Sunni and Shia. This study uses a qualitative approach to describe and elaborate on regional mapping and characteristics of modern Islamic philosophy (Sunni and Shia) study. The way to describe the data is through several expert opinions.. The data collection technique used in this study is library research (Library Research) where library research is the activity of collecting research-related materials from scientific journals, literature, and authors. This literature study was conducted to obtain theoretical information so that researchers have a strong theoretical basis for a scientific result. The author that the origins of the birth of Shia, and Sunni, have different backgrounds, in their respective different leadership developments, and have fundamental differences in understanding, especially in matters of thought, and have a unique development in which each is very interesting . for further study and research. In this regard, of course, the results of the discussion in this paper are not final, so it is suggested that further in-depth discussions and studies are highly expected.